(3eMGSHI GdJdhK GdHjFj (B/s - (3YHO GdQMef, ESeGYjd eMehOs ((3GdEScfOQjI(B: s (3ecJHI GdhaGA GdbGfhfjI(B, s, 2014)
(3jVe GdMGLI Edi JhXja eYdheGJ GdcdaI GdHjFjI aj UfY GdbQGQGJ GdESJKeGQjI , eaghe Yde GbJUGO GdHjFI , JfXje GdeOf GdUfGYjI hGOGQJgG OQGSI hJMdjd GdJcGdja GdHjFjI hCgejJgG aj JQTjO GdbQGQGJ GdEOGQjI , GdeTGcd GdeMGSHI GdeYGUQI , OhQ GdeMGSHI GdHjFjI aj EOGQI GdNWQ GdfGLe Yf GdJdhK GdHjFj hGdEaUGM YfgG , eMGSHI GdJdhK GdHjFj , GdeMGSHI Yf GdJcGdja GdHjFjIs
(3GdeQGLY U(B.420s
Keywords: (3GdHjFIs; (3GdJdhK GdHjFIs